Comparative study of hot air and vacuum drying on the drying kinetics and physicochemical properties of chicory roots - Balzarini, Maria Florencia (2018)
The effect of the drying conditions on the retention quality for dried chicory roots (Cichorium intibyus L.) was investigated. Cubes of chicory roots were dried using hot air and vacuum dryers at 60 and 80 °C. Two different air velocities (0.2 and 0.7 m/s) were used in the hot air dryer, and two vacuum pressures (25 and 50 mmHg absolute) were set in the vacuum chamber. An exhaustive three dimensional mathematical model to describe mass transfer during drying of chicory roots of 1 cm of side was presented considering a polynomial functionality for the contraction kinetics. Experimental data obtained at laboratory scale were used to validate the proposed model showing good agreement between the experimental and estimated moisture profiles for both drying procedures. Moisture diffusivity was found to increase with the air drying temperature, velocity and vacuum pressure depending on the drying method. However, higher moisture diffusivity coefficients and lower activation energy values were obtained for the vacuum drying method. Samples dried using the vacuum drier at 60 °C and 25 mmHg presented better retention quality attributes, i.e., better rehydration, lower shrinkage and higher total phenolic content. The proposed mathematical model was able to satisfactorily predict the described behavior.